1980
DOI: 10.1111/j.1476-5381.1980.tb10975.x
|View full text |Cite
|
Sign up to set email alerts
|

THE POTENT DEPOLARIZING ACTION OF PALYTOXIN ISOLATED FROM Palythoa Tubercurosa ON THE ISOLATED SPINAL CORD OF THE FROG

Abstract: The effects of palytoxin (PTX) isolated from Palythoa tubercurosa were tested on the isolated intra‐arterially perfused spinal cord of the frog. The resting and evoked potentials were recorded by means of a sucrose‐gap technique. PTX caused a marked depolarization of both ventral and dorsal roots. The minimum effective concentration was extremely low, approximately 10−11 m. During the depolarization the evoked ventral and dorsal root potentials were markedly reduced in amplitude. The ventral root reflex was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…On the other hand, electrophysiological studies revealed that the depolarizing action of PTX was attenuated by lowering the external Na concentration in cardiac muscle (23), skeletal muscle (5) and nerve tissue (17)(18)(19). These results suggest that the depolarizing action of PTX is due to the increase in Na permeability of the cell mem brane.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…On the other hand, electrophysiological studies revealed that the depolarizing action of PTX was attenuated by lowering the external Na concentration in cardiac muscle (23), skeletal muscle (5) and nerve tissue (17)(18)(19). These results suggest that the depolarizing action of PTX is due to the increase in Na permeability of the cell mem brane.…”
mentioning
confidence: 72%
“…Several toxicological studies suggested that the toxicity of PTX is due to its action on the cardiovascular system (5-8). The biological action of PTX has been extensively studied, and it was suggested that PTX acts on the cell membrane of the various organs investigated such as cardiac muscle (5, 9-12), skeletal muscle (5, 13), smooth muscle (10, 14-16), nerve tissue (17)(18)(19), red blood cells (20,21) and sperm (22).…”
mentioning
confidence: 99%
“…PTX increases the permeability for Na + and K + and induces membrane depolarization in various types of cells (Dubois and Cohen 1977;Ito et al 1979;Kudo and Shibata 1980;Pichon 1982). In the cardiovascular system, PTX induces contraction in the heart and vascular smooth muscle (Kaul et al 1974;Deguchi et al 1976;Ito et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…However, PTX-induced noradrenaline release was only partially inhibited by TTX and by Ca2 + removal. Since PTX induces TTX-insensitive membrane depolarization in skeletal muscle and nerve (Dubois & Cohen, 1977;Kudo & Shibata, 1980;Muramatsu et al, 1984), a portion of the PTX-induced noradrenaline release may not be due to a physiological exocytotic mechanism. Detailed mechanisms of the PTX-induced noradrenaline release remain to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The toxic action of PTX has been attributed to its profound vasoconstrictor effect (Ito et al, 1976). PTX depolarizes the membrane of various excitable cells (Rayner et al, 1975;Deguchi et al, 1976;Ito et al, 1976;1979;Dubois & Cohen, 1977;Kudo & Shibata, 1980;Muramatsu et al, 1984), possibly by increasing the permeability to Na' and K+ ions (Ozaki et al, 1983;Nagase et al, 1986). Mitani & Ito (1986) have studied the effect of PTX on cardiac cell membrane using the patch-clamp technique and found that the mem-1 Author for correspondence at the University of Tokyo.…”
Section: Introductionmentioning
confidence: 99%